Giving a combination of snails (Achatina fulica) and coconut dregs on the growth and protein content of maggots (Hermetia illucens) - Purnama, Intan; Ruyani, Aceng; Yani, Ariefa Primair; Johan, Henny; Parlindungan, Deni; Nursa’adah, Euis (Acta Aquatica: Aquatic Sciences Journal, 2025)
This study aims to determine the effect of providing a combination of snails and coconut dregs as feed on the growth and protein content of Black soldier Fly (BSF) maggots. The method used is an experiment with a Completely Randomized Design (CRD) consisting of five treatments and three replications. The treatments consist of: P1 (100% snails), P2 (75% snails: 25% coconut dregs), P3 (50%: 50%), P4 (25%: 75%), and P5 (100% coconut dregs). Maggot maintenance was carried out for 14 days with feeding carried out every 2 days in the morning at 10:00. The research data observed included Weight, Thickness, Length which were analyzed statistically using the ANOVA test and the test was continued with the Least Significant Difference (LSD) test, and the Kruskal wallis test if the data was not normal, temperature and humidity, Feed consumption, Specific growth rate (SGR), Waste reduction index (WRI), and Protein content and water content were analyzed using the automatic kjeldahl test. The results of the study showed that the provision of snail and coconut dregs feed had a very significant effect on the growth of maggots (P <0.05) both in weight and thickness, but had no significant effect (P>0.05) on the growth of maggot length. Treatment P1 (100% snail) gave the best results with an average weight of 0.09 g, a length of 13.4 mm, and the highest protein content of 27.49%. Treatment P5 (100% coconut dregs) showed the lowest results in all main parameters. It was concluded that snail feed was more optimal in supporting the growth and protein content of BSF maggots. The high animal protein content and soft texture are the main reasons, which show the potential of snails as a highly nutritious alternative feed for BSF maggot cultivation. Keywords: BSF Maggots; Coconut dregs; Growth; Snails